Alfonso García Robles, México, Nobel de la paz / presentación, selección y notas de Miguel Marín Bosch - Marín Bosch, Miguel; García Robles, Alfonso (1911-1991) (Frontera)
Lista de obras de Alfonso García Robles: p. 139-140